Advances in Network Performance Techniques Improving Confectionery Business Communication Reliability - Nwankwo Constance Obiuto,; Ugwu-Oju Ukamaka Mary,; Okeke Obinna ThankGod, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Advances in network performance techniques are increasingly critical to improving communication reliability across modern confectionery business environments. As manufacturers integrate digital tools including ERP, MES, SCADA systems, smart sensors, industrial IoT devices, and cloud-based platforms the demand for stable, high-speed, and resilient communication infrastructures has intensified. This abstract presents an overview of emerging network technologies and optimization strategies that enhance operational efficiency, data integrity, and real-time responsiveness in confectionery production and enterprise workflows. Keywords: network performance, communication reliability, confectionery manufacturing, IoT, SDN, QoS, edge computing, cyber-physical systems. Contemporary confectionery operations rely on seamless data exchange among interconnected production lines, automated dosing systems, temperature-controlled processes, and quality-monitoring platforms. Network performance techniques such as Software-Defined Networking (SDN) and Quality-of-Service (QoS) frameworks allow dynamic traffic prioritization, ensuring that time-sensitive control signals such as those used in moulding, enrobing, and packaging are delivered without delays or packet loss. High-speed industrial Ethernet, Wi-Fi 6/6E, and private 5G networks further strengthen communication stability by increasing bandwidth, reducing latency, and supporting dense device connectivity on factory floors and across supply-chain nodes. Edge computing is emerging as a cornerstone of communication reliability, enabling local processing of production data, predictive maintenance insights, and anomaly-detection algorithms without relying entirely on cloud infrastructures. This reduces communication bottlenecks and enhances system responsiveness in environments where continuous monitoring of thermal profiles, viscosity levels, or ingredient flow rates is essential. Additionally, redundancy mechanisms such as failover routing, dual-path architectures, and high-availability clusters protect against network interruptions that could disrupt production continuity or compromise food-safety monitoring. Real-time network analytics and AI-driven diagnostics are transforming communication reliability by identifying performance degradation, cybersecurity threats, or hardware faults before they escalate. As confectionery enterprises expand their digital footprints, these network performance techniques collectively ensure robust operational communication, minimize downtime, and support traceable, high-quality product outputs. Ultimately, advanced, resilient network infrastructures form the backbone of competitive, data-driven, and customer-responsive confectionery business ecosystems.